"Passing children" and precarious pathways: on the contingency of reproductive life courses in Cameroon. (September 2014) - Van Der Sijpt, Erica
Abstract This article explores the implications of reproductive mishaps for the life courses of women in eastern Cameroon. Based on 15 months of anthropological fieldwork in a Gbigbil village, it describes local ideas about the expected unfolding of physical and social life trajectories, and the ways in which reproductive losses jeopardize these anticipated pathways. The life history of one informant shows that repeated child death can create a paradoxical situation in which a woman feels, at the same time, physically old and socially young, and that decisions for the future are informed by these contradictory sensations. The particular dynamics brought about by reproductive loss, then, challenge common views of the life course as a predefined pathway through consecutive and clearly defined life stages. Instead, they reveal that reproductive biographies are contingent and unpredictable, and that life stages may be paradoxically congruent rather than mutually exclusive. This, in turn, affects the way in which women give direction to their precarious reproductive pathways.